The effect of choice of targeted market, production scale, and land tenure on the economics of integrated tilapia-prawn production - Rodrigues, Caio G. [UNESP]; Engle, Carole; Garcia Neto, Baltasar F. [UNESP]; Amorim, Rafael V. [UNESP]; Valenti, Wagner C. [UNESP] (Taylor & Francis, 2019)
Integrated aquaculture systems have the potential to enhance the environmental sustainability of aquaculture production, if economically feasible. Data from integrated tilapia-prawn production trials were used to develop economic-engineering enterprise budgets for ponds with and without substrate that targeted two different types of markets, using two production scales and two forms of land tenure. Inclusion of substrate increased investment and fixed costs and decreased net returns. Recreational markets (live tilapia for fee fishing and live prawns as bait) were profitable, but sales to supermarkets were not. Production scale and land tenure affected economic outcomes with increased pond size and leasing ponds demonstrating greater profitability. Results provide evidence of the need to carefully evaluate economic trade-offs associated with varying commercial-scale applications to increase the likelihood of adoption of new technologies.
Keywords: aquaculture scale; Economics; integrated aquaculture; land tenure; live bait; market channels